Analysis of Clay Mineral Transformation in Plambik Village, Central Lombok Using X-Ray Diffraction and Scanning Electron Microscope Methods - Nugroho, Totok; Prajoko, Bambang; Suryawan, I Gede Suryawan (Journal of Physics and Its Applications, 2023)
Analysis of minerals and microfabric changes during the burning process of clay in Plambik village, Central Lombok has been carried out using 2 methods: X-Ray Diffraction and Scanning Electron Microscope. A brick of dimension (10 x 20 x 5) mm was prepared which was formed through a gypsum mould. After drying it is burned using an electric furnace with temperatures: 800oC, 1000oC and 1100oC. The results show that using the X-ray diffraction method when burned at 800oC there are quartz minerals with several illite peaks, at 1000oC there is only quartz, the illite peaks disappear while at 1100oC the quartz mineral peaks remain accompanied by the appearance of mullit peaks. Then the effect of the firing temperature on the clay microfabric was analyzed by observing the sample with a Scanning Electron Microscope. This test aims to obtain information about the changes in structure and texture that develop during the combustion process and more specifically on the morphology of the particles and their interaction with the development of the vitrification process and the distribution of the shape and size of the pores. The results showed that before burning, the kaolinite and illite particles were randomly distributed with porous aggregates and the grain size was between 1 – 5 microns. During firing at 800oC some parts have undergone melting and welding phases with the development of secondary porosity. Meanwhile, when burning with a temperature of 1100oC, it appears that the welding and smelting processes that occur are wider and the emergence of mullite crystals from the glass matrix.